Efforts to Improve Learning Outcomes of Soccer Passing Through Game Modification - Dwi intani, Andini; Prayogo, Giri; Rizky Hafidzulloh Mulyadi; Pratama, Reza Resah (Universitas PGRI Palembang, 2025)
This research aims to improve learning outcomes Football Passing Through Game Modifications. The method used in this research is the Research Method Class Action (Classroom Action Research). This class action research has systematic steps consisting of action planning, implementation of actions, observation and reflection. This research is collaborative and participatory because it was carried out by the researchers themselves and observed by colleagues other physical education teachers. Based on the analysis of research result and discussion in this thesis, then it can be concluded that: At the beginning of the observation, it showed that basically the results students football passing learning is still far from expected. From there were 39 students, only 12 students or 31 % of students managed to complete it their learning. This shows that their learning process needs repair. In the first cycle of research process, student have shown changes attitude in learning. From the data obtained, as many as 27 students or 69% students are able to achieve grades according to minimum completeness criteria. In the second cycle of research, of the 39 students who were research subjects, 34 students or 87% of the total number of students were able to complete their learning outcomes according to the KKM, some students have even exceeded the KKM. This is real that achieving the target learning outcomes of football passing through modification the game can be achieved well.